Character Education Through Discussion Activities in STKIP PGRI Lubuklinggau Students - Susilo, Agus; Asmara, Yeni (Universitas Malikussaleh, 2020)
The current era of globalization makes humans very easy to reach an activity. Humans are basically creatures whose lives always undergo alternating phases. So in the current era of globalization, the world of education for the younger generation, especially students, requires character education that builds the nation's wisdom. Character education is through group study or discussion. The purpose of writing this research is to find out character education through discussion activities on STKIP PGRI Lubuklinggau students. The method used in this research is descriptive qualitative method, which uses observations, interviews, and literature studies to examine research studies. The results of the study note that innovative media in classroom learning in semester V students of STKIP PGRI History Education in Lubuklinggau is very necessary and very helpful in learning. Innovative media applied by lecturers in learning turns out to be able to shape the character of students who were previously passive and feel bored with the learning taught by the lecturer. Students feel there is a responsibility in participating in learning and trying to leave their laziness in the classroom. In addition, character education through discussion activities for STKIP PGRI Lubuklinggau students is very helpful in learning to respond to something and foster a high morale and foster a spirit of empathy.